Anatomic Variation of the Median Nerve Associated with an Anomalous Muscle of the Forearm - Atoni, Atoni Dogood; Oyinbo, Charles Aidemise (Folia Medica, 2017)
Documented anatomical variations are important not only for the study of the subject of anatomy, but also in clinical situation. This knowledge would aid surgeons in planning a preoperative strategy for surgical procedures and reconstructive surgery. The right forearm of a 35-year-old embalmed male cadaver present a splitting of the median nerve in the proximal 1/3 of the forearm to form medial and lateral divisions that accommodate an anomalous muscle. The split median nerve reunites at the distal 1/3 and continues as a single nerve. The anomalous muscle arises by muscle fibers from flexor digitorum superficialis and inserted by tendon into flexor digitorum profundus. There was no such variation in the left forearm. The knowledge of such anatomical variations is important to clinicians and surgeons in interpreting atypical clinical presentations and avoiding unusual injury during surgery.